Biodiversity of Andaman and Nicobar Islands in fantasy coinage - Das, I. (Philatelic Society of Kuching, Sarawak, 2017)
Fantasy coins are produced by enterprising individuals and companies, chiefly targetting collectors, rather than to defraud citizens, and considerable literature now exists on the topic (see listing in Cuhaj and Thomas, 2011; Cuhaj, 2012). Geographical entities linked to such products are sometimes curious and include coins purported to be from areas that are within legitimate political entities (such as Easter Island, Galapagos and Greenland), as (sometimes humorous) declaration of independence (including Republic of Texas, Hawaii Islands and Transdniestria), “online nations” or those entirely imaginary (including Atlantis and Lundy), or those that do not have human inhabitants (Antarctica, and even the Moon and Mars) or currencies for role-playing games and others (such as the board game, MonopolyTM). A specialist collectors group (The Unrecognised States Numismatic Society), based in California, USA, exists to encourage such hobbyists, which describes itself as “specialising in the study of coins, medallic pieces, banknotes and related numismatic, pseudonumismatic and exonumismatic material issued by unrecognised states, alternative governments, rebel and secessionist groups, political associations, alternative currency promoters, chivalric orders, new country projects, micronations and related entities, commercial organisations, artists, writers, film makers, royal pretenders and exiles, fantasists and utopian visionaries”